Immunology & Immune System - Zimmer P; Bansi J; Rademacher A; Schlagheck ML; Walzik D; Proschinger S; Bloch W; Joisten N (Deutsche Zeitschrift für Sportmedizin)
Increased levels of physical activity are associated with a risk reduction for several neurodegenerative disorders (e.g. Multiple Sclerosis, Parkinsons disease). Moreover, physical exercise is known to improve the physical capacity and to reduce commonlyobserved symptoms, such as motoric, cognitive and a ective impairments. In addition to the ameliorating e ects on speci c symptoms, rst evidence also suggests that physical exercise interventions may counteract and/or alleviate the progress of these diseases.Considering the side effects of drug therapy, exercise interventions represent a promising non-pharmacological supportive treatment option and are therefore increasinglybeinginvestigated in clinical research on neurological diseases.More knowledge about the underlying biological mechanisms is warranted in order to improve tailored exercise programs. However, the reduced accessibility of the central nervous system in humans and problems in the transferability of rodent models complicates research in this eld. Nevertheless, several peripheral markers indicating distinct biological pathways involved in the pathogenesis and progression of neurodegeneration have been revealed to date. Interestingly, these biomarkers have recently been described to be sensitive to exercise stimuli. In this review, we provide an overview of the interaction between potential mechanisms linked to physical exercise and the alleviation of neurodegenerative processes. More precisely, we focus on di erent aspects of exercise-induced impacts on neuronal growth factors, in ammation, blood-brain barrier permeability and the kynurenine pathway.KEY WORDS: Exercise, Physical Activity, Brain, Neurodegeneration, Neurological Disorders